Physical and Chemical Quality of Pork Landrace Crossbred That is Fed Based on Denpasar City Waste - F. P. I., Empang; Ariana, I N. T.; Putri, T. I. (Jurnal Peternakan Tropika, 2018)
The research was aimed to determine the comparisonof physicaland chemical quality pork of Landrace crossbred that is fed based on Denpasar city waste with pork of Landrace crossbred given concentrate.The research conducted for 2 months at the Laboratory of Animal Product Technology and Microbiology Faculty of Animal Husbandry, Agrokomplek Building Udayana University.The research used the meat of the Longissimus dorsi muscle from 16 crossbred Landrace pigs, male sex of castration, finisher phase with final body weight 90±0,53kg. The research used simple experimental design (t-Test) by comparing the physical and chemical quality of pork from Landrace crossbred that is fed based on Denpasar city waste (A) with pork of Landrace crossbred given concentrate (B), with each 8 pigs as replications. The variables observed were pH value, cooking loss, drip loss, water holding capacity, and water content. The data obtained were analyzed used two independent sample t-Test.The results showed that the pH values ??of both samples were the same, the percentage of water content of the two samples was significantly different (P<0.05), while the percentage of cooking loss, drip loss, and water holding capacity of both samples were not significantly different (P>0.05). Based on the results of the research can be concluded that, the physical and chemical qualitypork of Landrace crossbred that is fed based on Denpasar city wasteis lower than the physical and chemical quality pork of Landracecrossbred given concentrate. Keywords: Pork, Physical and Chemical Quality, Waste Treatment